Pyometra in a Tiger (Panthera tigris) - Cardoso, Eduardo Burgarelli Mayrink; Rahal, Sheila Canevese; da Silva, Jeana Pereira; Mesquita, Luciane dos Reis; Denadai, Renan; Mamprim, Maria Jaqueline; Pelaquim, Isadora Fernanda [UNESP]; Kobayashi, Priscila Emiko [UNESP] (Universidade Federal do Rio Grande do Sul, 2023)
Background: Captive tigers can live a long life, around 26 years. Among the diseases described some of non-infectious origin are quite common, such as chronic kidney disease, spondylosis, and biliary cysts or tumors. On the other hand, pyometra has been frequently reported in lions, who have a higher risk of developing the disease than tigers and leopards. Pyometra is a disease with few descriptions in tigers and it may be related to the physiological features of the species. The animal is listed as Endangered on the International Union for the Conservation of Nature Red List of Threatened. The present report aims to describe the diagnosis and treatment of pyometra in a captive tigress. Case: A 7-year-old entire female tiger (Panthera tigris) weighing 140 kg was presented with a 3-day history of anorexia and prostration. For clinical examinations, collection of laboratory and imaging tests, the patient initially underwent dissociative anesthesia to allow catheterization of the cephalic vein and intravenous general anesthesia for orotracheal intubation followed by anesthetic maintenance in isoflurane. On general physical examination, the animal had normal colored mucosa, vital parameters within normal limits, and a body condition score of 6 on a scale of 9. There was no presence of vulvar secretion. The blood count and the biochemical exams showed values within the normal range for the species. The chest X-ray in the right and left views did not demonstrate pulmonary abnormalities. Ultrasonographic examination of the abdomen showed distension of the uterine body and horns, which have intraluminal hyperechoic fluid content without flocculation. Based on the imaging exam, the diagnosis was suggestive of pyometra. Exploratory celiotomy was performed via ventral midline, confirming the condition, which was treated by ovariohysterectomy. The surgical technique was performed as described for therapeutic ovariohysterectomy in dogs and cats. Culture of uterine content identified Escherichia coli. The histological analysis identified diffuse endometritis associated with follicular cysts. The tiger had complete recovery without any complications. The patient was releasing 13 days after the surgical procedure and in the last contact four months after the surgery, it was in perfect health conditions. Discussion: Pyometra in large exotic felids has been occasionally reported, mainly in animals more than 10 years of age. Although the tigress in the report is estimated to be seven years old. The patient in question started with anorexia and prostration and as there was already a history of cystic endometrial hyperplasia, a possible pyometra was suspected, despite being uncommon in the species. There was not vaginal discharge. The definitive diagnosis was by means of ultrasound examination and ovariohysterectomy was performed. Abdominal surgery for these large felids is complex, due to the intra-abdominal volume the flank approach or by laparoscopic is suggested, however in this case a ventral midline incision was performed without intercurrences and complications in the post-operative period. The surgical technique like that used in small animals was effective for the treatment of pyometra in the tigress with the use of ovariohysterectomy. Culture of uterine content identified Escherichia coli, which has been the most commonly isolated pathogen in pyometra of large felids. It was concluded that, as in bitches with pyometra, early diagnosis and surgical treatment is ideal for the patient’s recovery.
Keywords: bacteria; infection; ovariohysterectomy; treatment